Upaya Peningkatan Kesadaran Masyarakat Terhadap Benda Peninggalan Sejarah Lubang Jepang Di Kelurahan Gunung Pangilun Kecamatan Padang Kota Padang - Juliandry Kurniawan Junaidi; Kaksim; Felia Siska; Irwan Irwan; Rozi Novita Sari; Parasianto (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of community service is to provide knowledge, motivation and increase public awareness about the importance of maintaining historical awareness through the preservation of historical objects in the Japanese hole in Gunung Pangilun Village, North Padang District, Padang City. Methods of Community Service, namely conducting outreach to the community and evaluation consisting of before evaluating the activity, at the time it was carried out and at the end of the activity which was made notes and then recapitulated. The results of this service show that the community increases knowledge and awareness of the importance of historical sites in the area where they live. This encourages the role of the community, protection and preservation of the reserve in preserving history as a cultural relic of the past.